ANALISIS MOTIVASI BELAJAR SISWA KELAS III SD NEGERI 1 PANANJUNG PADA MATERI PENGUKURAN PANJANG - Tresna Julianti, Risa; Alani, Nabella; Fajar Suryaningrat, Eko (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the learning motivation of third-grade elementary school students on the topic of length measurement. The background of this research is the variation in students learning motivation, which affects their engagement and understanding of mathematical concepts. This study employed a quantitative approach with a descriptive design. The population consisted of 30 third-grade students, and total sampling was applied. Data were collected using a questionnaire based on a four-point Likert scale. The instrument was tested for validity and reliability, resulting in 19 valid items out of 36 statements. Data analysis was conucted using descriptive statistics with the help of SPSS version 25. The findings revealed that students learning motivation was generally in the high category, with a mean score of 59.47, a standard deviation of 3.92, a minimum score of 46 and maximum score of 65. The majority of students (90%) were classified in the high category, while 6.67% were in the moderate category and 3.33% were in the very high category. These results indicate that most students demonstrate strong motivation in mathematics learning, particularly in length measurement.